Humanitarian responses in the protection gap - Ponthieu, A; Derderian, K (Refugee Studies Centre, University of Oxford, 2013)
Often a combination of factors pushes people to leave their country, and the voluntary character of their departure remains debatable, challenging humanitarians both to meet needs and to adapt to changing categories of forced displacement.